The birth and evolution of the Ministry of Health and of the National Health Service in Italy - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2015)
Current Ministries of Health (MH) have fundamental commitments in the body of modern States and exercise a number of functions that mainly regard the safeguard of human and animal health and medical- health planning and management. The many and various tasks of third millennium MH range from the surveillance of the safety of alimentary products, workplaces and the general environment to the organization of health professions and structures, from veterinary services to scientific research in the health context, from prevention of disorders to care and rehabilitation of diseases (1). [...]